Assessing the Impact of Sustainable Finance Regulation on Bank Risk: Evidence from Indonesia using a Difference-in-Differences Approach - Sutanto, Ahmad; Ermawati, Wita Juwita; Anggraeni, Lukytawati (JASF: Journal of Accounting and Strategic Finance, 2025)
Purpose: The purpose of this study is to examine the impact of the Financial Services Authority Regulation POJK 51/2017 about Sustainable Finance implementation on bank risk in Indonesia. The regulation mandates all commercial banks to integrate environmental, social, and governance principles into their strategic and operational frameworks. However, empirical evidence regarding how this policy affects financial stability remains limited. This research addresses that gap by analysing both the direct and indirect effects of the regulation on bank risk. Method: This study employs a quantitative method with a difference-in-differences approach to analyse the causal impact of implementing POJK 51/2017 on bank risk. The data used is a panel of 22 banks for the period from 2015 to 2024. In addition, a mechanism test is conducted to explore transmission channels through green credit and cost efficiency, as well as a heterogeneity test to measure differences in impact across bank size and ownership type. Findings: The research found that the implementation of POJK 51/2017 increased banking risk. Furthermore, a mechanism analysis showed that the green credit ratio serves as a transmission channel through which regulations influence risk, while the operational efficiency ratio does not. Furthermore, the impact is greater for small banks and state-owned banks. Implications: Banks must adopt risk-based green lending, especially for MSME-oriented projects that have higher information risks, while the Financial Services Authority should strengthen risk-based supervision by assessing the risk profile of green exposures rather than solely focusing on green credit volume. Novelty/Value: This study offers new empirical evidence by applying a difference-in-differences design to capture the causal impact of POJK 51/2017 on bank risk. It also identifies the green credit ratio as a main transmission channel and reveals differential risk effects across bank size and ownership, providing new insights into how institutional capacity shapes sustainable finance regulatory outcomes in Indonesia.